2021
DOI: 10.18632/aging.202338
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-butylphthalide inhibits neuroinflammation by stimulating foxp3 and Ki-67 in an ischemic stroke model

Abstract: Dl-3-n-butylphthalide (NBP) has been widely used to treat ischemic stroke in China. To investigate the mechanisms underlying NBP activity, we established a permanent middle cerebral artery occlusion (pMCAO) rat model and injected the rats with 4 mg/kg/d NBP for nine days. We then assessed neuroinflammation, neovascularization and nerve regeneration within the brain. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry imaging (MALDI-TOF MSI) was used to determine the phospholipid distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The preclinical studies revealed that NBP exerts neuroprotective effects in ischemic stroke both in vivo and in vitro , partially by promoting angiogenesis 30 , increasing BDNF expression 12 , promoting dendrite development 31 , protecting mitochondrial function 9 , inhibiting neuroinflammation 32 , and improving brain metabolism 33 . The clinical trials also demonstrated that NBP exerts anti-ischemic effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical studies revealed that NBP exerts neuroprotective effects in ischemic stroke both in vivo and in vitro , partially by promoting angiogenesis 30 , increasing BDNF expression 12 , promoting dendrite development 31 , protecting mitochondrial function 9 , inhibiting neuroinflammation 32 , and improving brain metabolism 33 . The clinical trials also demonstrated that NBP exerts anti-ischemic effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Till 1995, NBP was found to be useful for ischemic stroke and later experiments showed that both injecting NBP 3 h before or 2 h after surgery had improvement on infarction volume and motor functional recovery, and clinical studies showed that patients using NBP alone had better neurological function than control groups; however, there was no significant difference for the efficacy between NBP and tPA, so NBP had been used for stroke treatment in China ( Xu et al, 2019 ). Anti-inflammation was firstly found in the NBP-treated stroke model; NBP enhanced the proliferation of microglia and promoted the microglia polarization into M2 phenotype, an anti-inflammation phenotype, by activating the calcium/calmodulin-dependent protein kinase β (CaMKKβ)-AMPK pathway or PPARγ nuclear translocation; NBP also decreased the infiltration of endothelial cells by downregulating intercellular adhesion molecule 1 (ICAM-1) and protease-activated receptor-1 (PAR-1) ( Zeng et al, 2020 ; Liu et al, 2021b ). In addition, NBP played a role in promoting neuroplasticity, neurite outgrowth, and inhibiting neuron apoptosis, and the NgR, Mogo-A, and caspase 3 were decreased and growth factors such as BDNF, NGF, and neurite branches were increased ( Zhang et al, 2021 ).…”
Section: Traditional Chinese Medicine Therapymentioning
confidence: 99%
“…NBP has multiple pharmacologic effects in ischemic stroke, not only of endothelial protection but also of neuroprotection, anti-oxidation and anti-platelet aggregation [ 2 , 7 ]. In order to verify our hypothesis, we further compared the protective role of OHNBP and NBP in neuroprotection, anti-oxidation and anti-platelet aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, thrombolysis using intravenous recombinant tissue plasminogen activator (rtPA) is the only therapy approved by the FDA for ischemic stroke, while it can only be delivered to a small fraction of patients due to the narrow treatment window [ 1 ]. Other treatments including antiplatelet (such as clopidogrel, aspirin), neuroprotection (such as NBP) and antioxidant agents (such as edaravone) are also implemented in clinical practice, which provide limited benefits to patients [ 2 , 3 , 4 , 5 , 6 , 7 ]. A better understanding of stroke pathology is important to identify innovative targets to broaden our therapeutic options in this scenario.…”
Section: Introductionmentioning
confidence: 99%